Follow-up Care for Breast Cancer Survivors. (15th October 2019) - Ruddy, Kathryn J; Herrin, Jeph; Sangaralingham, Lindsey; Freedman, Rachel A; Jemal, Ahmedin; Haddad, Tufia C; Allen, Summer V; Hieken, Tina; Boughey, Judy C; Ganz, Patricia A; Havyer, Rachel D; Shah, Nilay D
Abstract: Breast cancer survivorship guidelines recommend at least annual follow-up visits, yet the degree to which this occurs in clinical practice is uncertain. Claims data from a US commercial insurance database (OptumLabs) were used to identify women treated with curative intent surgery for newly diagnosed breast cancer between 2006 and 2014. In 25 035 women, median follow-up was 3 years. In the second year after surgery, 9.6% of the patients did not visit a primary care provider, an oncologist, or a surgeon (guideline-nonadherent). The guideline-nonadherent proportion increased from 7.8% in women diagnosed in 2006 to 12.2% in those diagnosed in 2014 (two-sided Wald P < .001). During years 2–6, guideline-nonadherence was also associated with older age, nonwhite race, no radiation, no chemotherapy, no endocrine therapy, and increasing time after surgery. There is a substantial and increasing rate of inadequate follow-up among breast cancer survivors. This has the potential to impair outcomes.